(untitled) (Ludi Litterarri, 2026)
Edutainment, the integration of education and entertainment, has emerged as a significant pedagogical framework in elementary education, particularly as classrooms increasingly serve a generation of learners who are native users of digital technologies. This literature review examines how edutainment strategies, including digital game-based learning (DGBL), gamification, artificial intelligence (AI)-powered tutoring, interactive multimedia, digital storytelling, and augmented reality (AR), can enhance learning motivation, engagement, and academic achievement among primary school students. The review synthesizes evidence from 38 peer-reviewed studies and meta-analyses published between 2021 and 2025. Findings indicate that edutainment interventions produce meaningful effect sizes across multiple subject areas, with particular strength in STEM domains (d = 0.57–0.70) and affective outcomes such as motivation and engagement. The study further identifies key implementation barriers, including infrastructure limitations, teacher competency gaps, and curriculum alignment challenges, and proposes evidence-based recommendations to guide practitioners and policymakers. The paper concludes that thoughtfully designed edutainment environments, when grounded in constructivist and self-determination theories, can transform elementary classrooms into dynamic, learner-centered spaces that meet the cognitive and emotional needs of digital-generation students.